X-Ray Measurements of 44Ti in Four Supernova Remnants - Tyler E. Hanover; Mark D. Leising (The Astrophysical Journal)
We present the results of a search for scandium K _α X-ray fluorescence resulting from ^44 Ti electron capture decay in four young supernova remnants (SNRs). We analyze archival XMM-Newton data from Tycho’s SNR, Kepler’s SNR, Cassiopeia A, and SN 1987A. We fit the X-ray spectra in regions of interest with up to four components, thermal and power-law, as needed to fit the spectrum, and add a Gaussian to test for extra Sc emission. While all require the line with modest confidence, none represent definitive detections on their own, and all are consistent with previous gamma-ray detections or limits on the ^44 Ti mass.